Influence of multiple showering on quality of buffalo semen during hot-humid season - Hoque, Md. Raihanul; Rana, Md. Shohel; Nayan, Sourav Biswas; Miraz, Md. Faizul Hossain; Deb, Gautam Kumar; Nahar, Talukder Nurun; Habib, Raihan; Siddiki, Mohammad Shohel Rana (Journal of Advanced Veterinary and Animal Research, 2018)
Objectives: This experiment was conducted on buffaloes to see effect of showering on maintaining good quality of buffalo semen in hot season. Materials and methods: This study was conducted on 6(six) indigenous buffalo bulls in hot summer of March and April 2017. The effect of multiple showering vs single shower alone on fresh and equilibrated semen quality was observed. The buffalos were divided into similar two groups (according to age and weight) and housed in half-walled openshed with adequate spacing and the feeding management being identical. The bulls in the control group were allowed to a single shower at 10.00 am and experimental bulls were allowed to four showers at 07.00, 10.00, 13.00 and 16.00. Temperature and humidity were recorded during this time. The average temperature was around 35°C along with 72% relative humidity. The quality of experimental bull’s semen was evaluated in terms of volume, live sperm, sperm concentration, sperm motility, motion parameters and morphology for normal and abnormal sperm. For this analysis Computer Assisted Semen Analysis (CASA) system was used. Results: Between experimental group and control group semen quality differs significantly for volume (2.04±0.13 mL; 2.53±0.27 mL) (P<0.01); live sperm (81.38±1.22%; 90.28±1.53%) (P<0.01), normal fraction (36.87±6.38%; 47.87±12.01%) (P<0.05); DMR (6.89±5.86%, 5.86±1.45%) (P<0.05) and for proximal droplet (57.86±4.30, 45.26±10.96) (P<0.05). Motility and motion parameters for fresh semen were not significantly different. Conclusion: In short, showering showed significant effect on different parameters of fresh semen quality of buffalo but not in case of further processing. http://doi.org/10.5455/javar.2018.e239